Efeito da suplementação com benfotiamina sobre parâmetros de estresse oxidativo muscular de camundongos submetidos a treinamento de endurance - GONÇALVES, Álisson de Carvalho (2017)
The high levels of reactive oxygen species can trigger an imbalance in redox status, which generate oxidative damage in macromolecules. The present study aimed investigate the influence of oral supplementation with benfotiamine on oxidative stress and antioxidant activity in muscle of trained mice. Twenty-five male Balb/c mice was placed in groups: Pad-Sed) standard chow and sedentary (n=6); Ben-Sed: benfotiamine supplemented and sedentary (n=6); Pad-Tr: standard chow and trained (n=6); and Ben-Tr: benfotiamine supplemented and trained (n=7). Supplemented animals received chow AIN-93G with benfotiamine. Trained mice was submitted to 6-weeks endurance swimming training, with an exhaustion test at the end. The concentration of free malondialdehyde (MDA), proteins bound to malondialdehyde (PrMDA) and non-protein thiols as well as the activity of catalase (CAT) and superoxide dismutase (SOD) were analyzed in the gastrocnemius muscle. There was no difference in the time of exhaustion resistance and the post-exhaustion lactate concentration. The concentration of MDA was lower in the Ben-Tr group than in the sedentary groups. The concentration of PrMDA was higher in the Pad-Sed group than in the other groups. Thiol levels were higher in the Ben-Sed group than in the non-supplemented groups. CAT activity was more pronounced in both supplemented groups. SOD was more efficient in the Ben-Tr group than in the non-supplemented groups. The results showed that benfotiamine supplementation is an efficient antioxidant strategy capable of preventing muscle oxidative damage in individuals engaged in endurance training programs. In conclusion, benfotiamine is effective in preventing muscle oxidative damage and does not interfere in endurance performance.